A major role for RCAN1 in atherosclerosis progression. Issue 12 (15th October 2013) - Méndez‐Barbero, Nerea; Esteban, Vanesa; Villahoz, Silvia; Escolano, Amelia; Urso, Katia; Alfranca, Arantzazu; Rodríguez, Cristina; Sánchez, Susana A.; Osawa, Tsuyoshi; Andrés, Vicente; Martínez‐González, José; Minami, Takashi; et al.
<x xml:space="preserve">Abstract</x> Atherosclerosis is a complex inflammatory disease involving extensive vascular vessel remodelling and migration of vascular cells. As RCAN1 is implicated in cell migration, we investigated its contribution to atherosclerosis. We show RCAN1 induction in atherosclerotic human and mouse tissues. Rcan1 was expressed in lesional macrophages, endothelial cells and vascular smooth muscle cells and was induced by treatment of these cells with oxidized LDLs (oxLDLs). Rcan1 regulates CD36 expression and its genetic inactivation reduced atherosclerosis extension and severity in Apoe−/− mice. This effect was mechanistically linked to diminished oxLDL uptake, resistance to oxLDL‐mediated inhibition of macrophage migration and increased lesional IL‐10 and mannose receptor expression. Moreover, Apoe−/−Rcan1−/− macrophages expressed higher‐than‐Apoe−/− levels of anti‐inflammatory markers. We previously showed that Rcan1 mediates aneurysm development and that its expression is not required in haematopoietic cells for this process. However, transplantation of Apoe−/−Rcan1−/− bone‐marrow (BM) cells into Apoe−/− recipients confers atherosclerosis resistance. Our data define a major role for haematopoietic Rcan1 in atherosclerosis and suggest that therapies aimed at inhibiting RCAN1 expression or function might significantly reduce atherosclerosis burden.